Drug Delivery Systems: Study of Inclusion Complex Formation between Methylxanthines and Cyclodextrins and Their Thermodynamic and Transport Properties - Santos, Cecília I. A. V. (2019)
This paper presents an analysis of the molecular mechanisms involved in the formation of inclusion complexes together with some structural interpretation of drug-carrier molecule interactions in aqueous multicomponent systems comprising methylxanthines and cyclodextrins. The determination of apparent partial molar volumes (Φv) from experimental density measurements, both for binary and ternary aqueous solutions of cyclodextrins and methylxanthines, was performed at low concentration range to be consistent with their therapeutic uses in the drug-releasing field. The estimation of the equilibrium constant for inclusion complexes of 1:1 stoichiometry was done through the mathematical modelling of this apparent molar property. The examination of the volume changes offered information about the driving forces for the insertion of the xanthine into the cyclodextrin molecule. The analysis on the volumes of transfer, Δ, Φv,c and the viscosity B-coefficients of transfer, ΔB, for the xanthine from water to the different aqueous solutions of cyclodextrin allowed evaluating the possible interactions between aqueous solutes and/or solute-solvent interactions occurring in the solution. Mutual diffusion coefficients for binary, and ternary mixtures composed by xanthine, cyclodextrin, and water were measured with the Taylor dispersion technique. The behavior diffusion of these multicomponent systems and the coupled flows occurring in the solution were analyzed in order to understand the probable interactions between cyclodextrin-xanthine by estimating their association constants and leading to clearer insight of these systems structure. The measurements were performed at the standard (298.15 ± 0.01) K and physiological (310.15 ± 0.01) K temperatures.